1998
DOI: 10.1007/bf02760816
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the production of highly competent cells ofAgrobacterium for transformation via electroporation

Abstract: The introduction of binary plasmids into Agrobacterium hosts for Agrobacterium-mediated transformation of plants is most readily achieved by electroporation. However, occasionally, no transformed colonies are recovered and the transformation program is delayed. Poor transformation rates are commonly associated with particular combinations of Agrobacterium strains and plasmid-selection markers. In order to avoid this problem, it is important for the bacteria to have a highly competent status for reception of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 5 publications
1
37
0
Order By: Relevance
“…Anthocyanin pigmentation has been reported to be induced in immature embryos, shoot apical meristems, and aleurone layer of wheat, sorghum, barley and rice by the maize transcription factors of anthocyanin, C1/Lc or C1/Bperu (Bilang et al 1993, Casas et al 1993, McCormac et al 1998, Maekawa et al 2000. The present results also showed that C1/B-peru could activate the genes for anthocyanin synthesis in wheat coleoptiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthocyanin pigmentation has been reported to be induced in immature embryos, shoot apical meristems, and aleurone layer of wheat, sorghum, barley and rice by the maize transcription factors of anthocyanin, C1/Lc or C1/Bperu (Bilang et al 1993, Casas et al 1993, McCormac et al 1998, Maekawa et al 2000. The present results also showed that C1/B-peru could activate the genes for anthocyanin synthesis in wheat coleoptiles.…”
Section: Discussionmentioning
confidence: 99%
“…However, GUS activity has been examined only by an in vitro assay procedure and detected histochemically as diffused blue spots. Recently, the modified gene of green fluorescent protein (GFP), expressed in plant cells and allowed non-lethal detection under a fluorescent microscope, has been used as a reporter (McCormac et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Competent Agrobacterium tumefaciens (strain GV3101; pMP90) were prepared using the protocol of McCormac et al (1998). Arabidopsis (Col-0/vtc1) plants were transformed with Agrobacterium containing the NPR1-GFP construct (pBI 1.4t backbone; Kinkema et al, 2000) using a simple dip transformation technique (Clough and Bent, 1998).…”
Section: Plant Transformationmentioning
confidence: 99%
“…The NS3 gene was inserted into the multicloning site of SpeI/EcoRI-digested pGreen0229 to place it under the control of 35S promoter to give construct pGreen0229-35S:NS3 (35S-NS3). The 35S-NS3 was transferred into A. tumefaciens strain AGL1, with helper plasmid (pJIC) by electroporation (McCormac et al, 1998).…”
Section: Methodsmentioning
confidence: 99%